2018
DOI: 10.15376/biores.14.1.166-179
|View full text |Cite
|
Sign up to set email alerts
|

Load-carrying capacity of self-tapping lag screws for glulam-lightweight concrete composite beams

Abstract: When a lag screw with a large diameter is used as the shear connector in timer-concrete composite beams, the procedure of pre-drilling is required during the construction process. In this paper, a new type of lag screw was proposed to omit the pre-drilling step. To investigate the shear behavior of the self-tapping lag screws for glulam-lightweight concrete composite beams, a total of 18 push-out tests were conducted. Based on the push-out test results, the influences of concrete type, screw diameter, and pene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In the timber-concrete connection, according to experimental tests, the coefficient of friction between concrete and timber is µ = 0.45-0.66 [42,43]. Using the simplified EYM model and based on the experimental tests, Hao Du et al [44] concluded that the angle of rotation of the screw has a significant part in contributing to the load-carrying capacity due to the rope effect. The coefficient of friction is in the range of 0.35-0.50 (µ = sin(90 − θ)) for an angle θ that varies from 20 to 30 degrees (for the slip in connection up to 15 mm).…”
Section: Embedmentmentioning
confidence: 99%
“…In the timber-concrete connection, according to experimental tests, the coefficient of friction between concrete and timber is µ = 0.45-0.66 [42,43]. Using the simplified EYM model and based on the experimental tests, Hao Du et al [44] concluded that the angle of rotation of the screw has a significant part in contributing to the load-carrying capacity due to the rope effect. The coefficient of friction is in the range of 0.35-0.50 (µ = sin(90 − θ)) for an angle θ that varies from 20 to 30 degrees (for the slip in connection up to 15 mm).…”
Section: Embedmentmentioning
confidence: 99%
“…Currently, there are no relevant reports on the composite structures of glubamgeopolymer concrete. However, a significant number of studies on the connection mechanism, flexural performance, long-term performance, and design method of timberconcrete composite (TCC) structures have been conducted by a large number of academics (Clouston et al 2005;Du et al 2019;Jiang et al 2021). These have been widely used in floor structures and bridges (Yeoh et al 2011a), and the shear connectors have been a focus of research, since the service performance of the composite structure depends on the appropriate connection of two materials.…”
Section: Introductionmentioning
confidence: 99%